EXPERIENCE FROM THE IMPLEMENTATION OF IMMERSION PROGRAM AS A GLOBAL TRAJECTORY - Deni Sapta Nugraha (Langit Biru: Jurnal Ilmiah Aviasi, 2019)
The purpose of this study was to uncover there main research questions; how was the immersion program of ICAI conducted to improve English language skills?, How was the view point of the participant in carrying out the program, and how effective was the program to achieve English language skills. This research was analyzed descriptively by using questionnaire, observation, and interview. The results showed that the immersion program was well conducted and gave some improvement in the mastery of English language skills especially speaking skills. The participants also gave a positive point of view that it helped to improve their English expertise. Based on the questionnaire and observation, there are also several other improvements such as teaching techniques mastery, English delivery in content-area teaching and their confidence to use English as a means of communication for their content-area teaching in the classroom. In conclusion, the program has boosted the participants to increase their speaking skill.